The assessment of chemical composition and biological activity of faba bean pods as a potential feed additive utilized in piglets nutrition - Inna Vlasova; Philip Krüsselmann; Yuliia Kostenko; Maciej Obrębski; Sebastian Granica; Wilfried Vahjen; Jürgen Zentek; Marcin Równicki; Jakub P. Piwowarski (Scientific Reports)
Abstract The study addresses the utilization of food waste by-products from faba bean (Vicia faba L.) pods (FBP) as an alternative feed supplement to promote sustainable piglet growth by reducing antimicrobial use. Objectives include evaluation of FBP in terms of nutritional components (proximate composition, fibres, minerals), phytochemical composition (total phenols, HPLC-MS profiling), and in vitro biological activities. Air-dried FBP from the cultivar ‘Bizon’ contained high levels of crude protein (144 g/kg), dietary fibre (413 g/kg), potassium (27.8 g/kg), and iron (126 mg/kg). Phytochemical analysis of methanolic extract from FBP revealed significant levels of polyphenols, including vestitol, piscidic acid, hydroxyeucomic acid, quercetin, and kaempferol glycosides with no detectable tannins. The extract showed negligible activity against porcine digestive enzymes (α-amylase, lipase, and trypsin) (IC50 > 4 mg/mL) and demonstrated a dose-dependent antibacterial activity against Escherichia coli and Salmonella enterica in concentrations of 1–8 mg/mL. The extract had low cytotoxicity (IC50 = 432.6 µg/mL) against IPEC-J2 – cells derived from porcine jejunal epithelium. The results indicate that FBP ‘Bizon’ is a valuable source of bioactive compounds with antibacterial properties, without adverse effects on porcine enzymes or IPEC-J2 cells, supporting its potential as a sustainable feed in piglet nutrition, in line with circular economy concepts.